2018
DOI: 10.1248/cpb.c17-00779
|View full text |Cite
|
Sign up to set email alerts
|

Semi-synthesis of Twelve Known 20<i>Z</i>/<i>E</i> Pseudo-Ginsenosides and Their Comparative Study of Antioxidative Activity in Free Radical Induced Hemolysis of Rabbit Erythrocytes

Abstract: SummaryTweleve pseudo-ginsensides were synthesized under a mild condition, via a simple three-step called acetylation, elimination-addition and saponification. The inhibitory effects of these tweleve pseudo-ginsenosides were screened on the hemolysis of rabbit erythrocytes caused by 2,2 ' -azobis (2-amidinopropane hydrochloride) (AAPH). It was found that the IC 50 values followed the sequence of (20Z) pseudo-protopanaxatriol (pseudo-PPT) < (20Z) pseudo-protopanaxadiol (pseudo-PPD) < (20Z) pseudo-Rh2 < (20E) ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Although the naturally occurring dammarane-type saponins have been studied for a long time [102], SAR studies revealed that chemically generated synthetic saponins were mainly on ginsenoside derivatives and were still far from satisfactory [103,104]. Based on the recent progress in organic synthesis (Figure 4) [105,106], several studies showed cytotoxicity against cancer cells [58,107,108], as well as antioxidative [59], antiasthma [60] and skin-protective effects [61] of ginsenoside derivatives (Table 1).…”
Section: Dammaranementioning
confidence: 99%
See 1 more Smart Citation
“…Although the naturally occurring dammarane-type saponins have been studied for a long time [102], SAR studies revealed that chemically generated synthetic saponins were mainly on ginsenoside derivatives and were still far from satisfactory [103,104]. Based on the recent progress in organic synthesis (Figure 4) [105,106], several studies showed cytotoxicity against cancer cells [58,107,108], as well as antioxidative [59], antiasthma [60] and skin-protective effects [61] of ginsenoside derivatives (Table 1).…”
Section: Dammaranementioning
confidence: 99%
“…Modifications to the C-20 side chain of the ginsenosides demonstrated that the hydroxylation site and configuration at C-20 and C-24 profoundly influenced cytotoxicity, in which ginsenoside derivatives bearing a monosaccharide at C-3 and a disaccharide at C-6 were more cytotoxic than those without modification [58,107,108]. Another study found that ginsenosides incorporating a Z-configuration at C-20 exhibited higher antioxidative activity than those not, and those bearing a disaccharide moiety at the C-3 position exerted a stronger hemolytic effect [59]. In other work, Li and co-workers evaluated the in vivo anti-IgE activity of a series of ginsenoside compound K (CK and 28, Figure 4) analogues in an ovalbumin (OVA)-induced asthmatic mouse model; compounds modified at C20 and ketoxime exhibited a comparable antiasthmatic effect to CK [60].…”
Section: Dammaranementioning
confidence: 99%
“…13) For AAPH-induced oxidative hemolysis experiments, most of the published studies to date also used absorbance at about 540 nm to analyze the extent of hemolysis. 8,10,11,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The absorption spectrum of erythrocytes that we observed after water-induced hemolysis had peaks at 541 and 576 nm (Fig. 1A).…”
Section: Discussionmentioning
confidence: 76%
“…Many studies have used AAPH-induced oxidative hemolysis to measure antioxidant activity of various compounds, especially complex mixture compounds. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] In the present study, we re-examined the methodology of AAPH-induced oxidative hemolysis and propose an improved method for evaluating antioxidant activity of various compounds, especially lipophilic compounds, using AAPH-induced hemolysis of erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Lipids constitute the bilayer skeleton of cell membrane, cholesterol is inserted between phospholipids to enhance the stability of bilayer, proteins are irregularly embedded or floated in its surface, and can move freely in the membrane plane. The flow or contraction of membrane proteins make red blood cells be more plastic, which can pass through the microcirculation without being blocked or destroyed [2,3]. The unique flexibility and deformability of red blood cells are derived from their own membrane structure.…”
Section: Introductionmentioning
confidence: 99%